2012
DOI: 10.30843/nzpp.2012.65.5370
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine fumigation to disinfest kiwifruit

Abstract: Global use of phosphine as a fumigant has increased in response to the need to replace methyl bromide and with the improved formulations ECO2FUME and VAPORPH3OS Phosphine is registered as a postharvest fumigant on kiwifruit in New Zealand and has been used commercially to reduce the risk of detecting live pests Scale insects mealybugs and diapausing twospotted spider mites were exposed to a range of phosphine treatments A 48h low temperature (1746C) fumigation (64083311 ppm) achieved 100 mortality of all life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…However, it still takes days to control the target pest. [14][15][16][17][18][19][20][21] It has been reported that MB and PH 3 mixtures exert synergistic effects on stored product pests, such as Sitophilus granaries and Tribolium castaneum, 22,23 therefore we hypothesized that fumigation with MB and PH 3 mixtures could have potential for postharvest control of fruit flies. In the present study, we tested the efficacy of short-period fumigation (2.5 h) with PH 3 and MB gaseous mixtures at disinfesting B. dorsalis, and evaluated the post-treatment quality of Nanfeng mandarin fruits.…”
Section: Introductionmentioning
confidence: 99%
“…However, it still takes days to control the target pest. [14][15][16][17][18][19][20][21] It has been reported that MB and PH 3 mixtures exert synergistic effects on stored product pests, such as Sitophilus granaries and Tribolium castaneum, 22,23 therefore we hypothesized that fumigation with MB and PH 3 mixtures could have potential for postharvest control of fruit flies. In the present study, we tested the efficacy of short-period fumigation (2.5 h) with PH 3 and MB gaseous mixtures at disinfesting B. dorsalis, and evaluated the post-treatment quality of Nanfeng mandarin fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, PH3 fumigation has been used to control insects affecting agricultural products requiring lowtemperature storage conditions for fresh preservation (Jamieson et al 2012). In this case, scale insects (mealybugs) can be controlled by fumigation with about 3000 ppm PH3 gas for 36 h at 1-3°C.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, scale insects (mealybugs) can be controlled by fumigation with about 3000 ppm PH3 gas for 36 h at 1-3°C. Currently, ECO2FUME (Cytec Industries Inc., West Paterson, NJ, USA), a mixture of 2% PH3 with 98% CO2, is used commercially for the disinfestation of stored products and nursery trees in quarantine facilities (Jamieson et al 2012;Moon et al 2012). However, the control efficacy of PH3 fumigation is known to be higher at higher temperatures than at lower temperature (Liu 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These larvae were pink, not laccid, but only capable of slight movements and when these barely alive larvae were examined 10 days after treatment, most remained moribund. While appearing to be near dead, as discussed by Jamieson et al (2012), a phytosanitary inspector will justiiably determine moribund larvae to Figure 1 Mortality (mean ± SEM corrected for control mortality) of ifth instar codling moth larvae within apples exposed to different phosphine concentrations for 48 or 72 h at 0.5 or 12°C.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphine has a long history as a product for disinfesting grain (Chaudhry 1997) and recently has been used as a pest mitigation treatment at cool-storage temperatures for a wide variety of fresh produce in Chile (Horn et al 2010) and for kiwifruit in New Zealand (Jamieson et al 2012). An eficacious fumigant against codling moth could replace methyl bromide for the Japanese market and facilitate access for New Zealand apples to other countries where codling moth is not present.…”
Section: Introductionmentioning
confidence: 99%